Bortezomib-based induction, high-dose melphalan and lenalidomide maintenance in myeloma up to 70 years of age - Mai, Elias K.; Miah, Kaya; Bertsch, Uta; Dürig, Jan; Scheid, Christoph; Weisel, Katja; Kunz, Christina; Munder, Markus; Lindemann, Hans-Walter; Merz, Maximilian; Hose, Dirk; Jauch, Anna; et al. (Leukemia, 2021)
Intensive upfront therapy in newly-diagnosed multiple myeloma (MM) including induction therapy (IT), high-dose melphalan (MEL200), and autologous blood stem cell transplantation (ASCT) followed by consolidation and/or maintenance is mostly restricted to patients up to 65 years of age. Prospective phase III trial data in the era of novel agents for patients up to 70 years of age are not available. The GMMG-MM5 trial included 601 patients between 18 and 70 years of age, divided in three groups for the present analysis: ≤60 years (S1, n = 353), 61-65 years (S2, n = 107) and 66-70 years (S3, n = 141). Treatment consisted of a bortezomib-containing IT, MEL200/ASCT, consolidation, and maintenance with lenalidomide. Adherence to treatment was similar among patients of the three age groups. Overall toxicity during all treatment phases was increased in S2 and S3 compared to S1 (any adverse event/any serious adverse event: S1:81.7/41.8% vs. S2:90.7/56.5% vs. S3:87.2/68.1%, p = 0.05/<0.001). With respect to progression-free survival (log-rank p = 0.73), overall survival (log-rank p = 0.54) as well as time-to-progression (Gray’s p = 0.83) and non-relapse mortality (Gray’s p = 0.25), no differences were found between the three age groups. Our results imply that an intensive upfront therapy with a bortezomib-containing IT, MEL200/ASCT, lenalidomide consolidation, and maintenance should be applied to transplant-eligible MM patients up to 70 years of age.
Published: 20 July 2020
Gesehen am 14.09.2021